(untitled) - Morgan, Monroe T. (Belmont, CA, 2003)
This text emphasizes the environmental practices that support human life as well as the need to control factors that are harmful to human life. Chapters focus on the requisites of life, water, air, food, space, and shelter. Chapters also address proper management of wastewater treatment, solid waste management, insect and rodent control and agents that cause diseases
Keywords: Environmental health.,Health risk assessment.,Sức khỏe môi trường,Đánh giá các nguy cơ về sức khỏe